Perbandingan Algoritma A* (A star) dan Algoritma IDA* (Iterative Deepening A* Pada Permainan Sliding Puzzle - Puguh Riawang; Mamika Ujianita Romdhini; Irwansyah - (University of Mataram, 2019)
One of the games discussed in this study is a puzzle game. In a puzzle game players are expected to be able to achieve the final goal to form a correct picture or pattern. The algorithms used in this study are the A* algorithm (A Star) and IDA* algorithm (iterative deepening A*). This study aims to determine the completion process of the game Sliding Puzzle using A* Algorithm and IDA* Algorithm and determine which algorithms are more efficient. Based on the time complexity it was found that the A* algorithm is more efficient than the IDA* algorithm because it only chooses the smallest value of f, apart from the IDA* algorithm which tries all possible steps with the same value of f. The disadvantages of these two algorithms are that in some cases this algorithm cannot solve the problem or stop at the local optimum or the same step repeated.